6C.07: INCREASE THE PREDICTIVE CAPACITY OF CORONARY RISK WITH A GENETIC SCORE. (June 2015) - Pereira, A.; Reis, R. Palma Dos; Gomes, S.; Rodrigues, R.; Oliveira, R.; Sousa, A.C.; Rodrigues, M.; Freitas, S.; Guerra, G.; Freitas, A.I.; Borges, S.; Ornelas, I.; et al.
Abstract : Objective: Genes associated with coronary artery disease (CAD) and traditional cardiovascular risk factors (TCRF) present a limited individual predictive value. It is expected that the inclusion in global scores may increase the predictive ability. In genetic terms, there are no validated risk scores to predict the occurrence of cardiovascular disease or its complications. Objective: Evaluate the ability of a multifactorial genetic risk score (GRS) be able to add predictive power, for the development of CAD, to the model developed only with TCRF. Design and method: A case-control study was performed with 1321 consecutive coronary patients (mean age 53.4 ± 8.1 years, 78.8% male) and 1148 controls selected to be similar to cases in terms of gender and age. Traditional risk factors (hypertension, diabetes, dyslipidemia, smoking, obesity, sedentary lifestyle, family history) were evaluated according to the International criteria. The genetic variants were analyzed with specific primers and the GRS was determined in the entire population, based on 29 genetic polymorphisms previously associated with atherosclerotic disease in general and, in particular, with CAD. A multiplicative model was then used based on risk multiplication (odds ratio - OR) of each genotype of the 29 studied genes. Subsequently, a multivariate analysis was done with the TCRF only or the TCRF with the GRS and a ROC curve was constructed for both situations. Results: After multivariate analysis, the GRS was found to be an independent predictor for CAD (OR = 2.1; CI: 1.7–2.5; p < 0.0001). The AUC increased from 0.71 to 0.74 after the inclusion of GRS to the TCRF in the multivariate analysis (Figure). Figure. No caption available. Conclusions: In our population, the multiplicative GRS was an independent predictor for CAD. When analyzed together with traditional risk factors, it adds little predictive value. Its usefulness, in clinical practice, may be directed to the intermediate risk group, in which a possible risk reclassification can have different therapeutic measures.